Foundations in social neuroscience - Cacioppo, John T., 1951-2018 (Social neuroscience series., 2002)
Annotation A full understanding of the biology and behavior of humans cannot be complete without the collective contributions of the social sciences, cognitive sciences, and neurosciences. This book collects eighty-two of the foundational articles in the emerging discipline of social neuroscience. The book addresses five main areas of research: multilevel integrative analyses of social behavior, using the tools of neuroscience, cognitive science, and social science to examine specific cases of social interaction; the relationships between social cognition and the brain, using noninvasive brain imaging to document brain function in various social situations; rudimentary biological mechanisms for motivation, emotion, and attitudes, and the shaping of these mechanisms by social factors; the biology of social relationships and interpersonal processes; and social influences on biology and health.